(untitled) (Web of Teachers: Inderscience Research, 2024)
This article is devoted to the application of deductive and inductive approach in teaching process. Grammar instruction plays a crucial role in language learning, and various teaching methodologies are used to help students master it. Two prominent approaches are the deductive and inductive methods. The deductive method involves explaining grammatical rules explicitly before having students practice applying them, while the inductive method encourages students to discover rules themselves through exposure to language examples. Both methods have distinct advantages and drawbacks, and research suggests that their effectiveness may depend on the learners’ proficiency level, cognitive styles, and the teaching context. This article explores the characteristics, advantages, and challenges of each method and provides recommendations for integrating both approaches in grammar teaching to cater to diverse student needs.